2012
DOI: 10.1093/ejcts/ezr204
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary outcomes of conventional aortic valve replacement in 638 octogenarians: insights from an Italian Regional Cardiac Surgery Registry (RERIC)

Abstract: This study, showing that contemporary outcomes after AVR are excellent, may help to improve treatment decision-making in elderly patients with aortic valve disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
27
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 24 publications
6
27
3
1
Order By: Relevance
“…Recent observational studies have demonstrated that elderly patients or those with depressed left ventricular function or affected by systemic coexisting disorders are at increased risk for operative mortality or morbidity. 5,[9][10][11][12][13] To cast further light on these issues, we conducted this registry study reporting outcomes from a large regional series of high-risk patients undergoing SAVR, with or without associated coronary artery bypass grafting (CABG) from 2008 through 2013 in Emilia Romagna (ER), Italy. The main purpose was to assess 30-day mortality and morbidity, and 5-year outcomes (all-cause mortality, cardiac related death, stroke, re-operation, definitive pacemaker implantation); the second aim was to identify and discuss the potential risk factors for increased early and late mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Recent observational studies have demonstrated that elderly patients or those with depressed left ventricular function or affected by systemic coexisting disorders are at increased risk for operative mortality or morbidity. 5,[9][10][11][12][13] To cast further light on these issues, we conducted this registry study reporting outcomes from a large regional series of high-risk patients undergoing SAVR, with or without associated coronary artery bypass grafting (CABG) from 2008 through 2013 in Emilia Romagna (ER), Italy. The main purpose was to assess 30-day mortality and morbidity, and 5-year outcomes (all-cause mortality, cardiac related death, stroke, re-operation, definitive pacemaker implantation); the second aim was to identify and discuss the potential risk factors for increased early and late mortality.…”
Section: Introductionmentioning
confidence: 99%
“…26 More recently, Di Eusanio et al reported 4.5% operative mortality in a large regional series of 638 octogenarians undergoing isolated AVR surgery, with a mean logistic EuroSCORE I of 13.0%±7.9, very similar to our results. 12 In another large series, Saxena et al reported a 4.0% 30-day mortality rate in 531 octogenarians undergoing isolated AVR surgery. Although no formal surgical risk score calculation was mentioned, precluding a more accurate comparison, these results are also in agreement with the present series.…”
Section: Operative Resultsmentioning
confidence: 96%
“…In our Center, in 2010-2012, TAVI was performed in 73 patients aged 76 ± 9 (52-90), in 51% of men and 49% of women, with a mortality rate of 3.4%. By contrast, the number of deaths after surgical valve replacement in patients aged ≥75 was as high as 21.9% (8)(9)(10)(11).…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, OPCAB should be opted for, thus avoiding a number of complications. Increasingly frequently, older patients undergo hybrid surgery which consists in combining surgical techniques with catheterization (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%